(untitled) (Neo Science Peer Reviewed Journal, 2022)
Today’s specialist, no matter what field he works in, needs to be aware of events and events related to his field and to constantly improve his knowledge. The introduction of modern information and communication technologies into the educational process has led to the creation of a new form of education - distance education, in addition to traditional teaching methods. Definitions have been reviewed.